PENGARUH PENAMBAHAN MADU PADA PEMBUATAN PERMEN JELLY KOLANGKALING (Arenga pinnata) - Nofita Rahayu Silaen; Sentosa Ginting (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
This research is done aims to study the making of candy jelly sugar palm fruit with the addition of honey and to know the best gelatin concentration on making jelly sugar palm fruit (Arenga pinnata). This study was conducted using two factotes namely one factor of addition of honey and factor two gelatin concentration. And the parameters are water cramped test, ash content, crude fiber, reducing sugar analysis, TSS, organoleptic test of color, flavor, essences and texture. From the research results obtained as follows : based on the results of this study it can be concluded that with the addition of honey to the making of jelly sugar palm fruit give a very reak effect on P< 0,01 level to water content, ash content, reducing sugar, TSS, texture, color, essence an taste, while different not significant at P<0,05 to crude fiber. The addition of gelatin concentration has very significant effect on P<0,05 to crude fiber, reducing sugar, TSS, color essence and taste.